2022
DOI: 10.1007/s00467-022-05559-5
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the experiences and well-being of siblings of children with chronic kidney disease: implications for practice and research

Abstract: Background Children with chronic kidney disease (CKD) and their families deal with challenging circumstances. While numerous studies have shown that both patients and parents in these families can experience a variety of challenges and concerns, the experience of siblings is less well understood. The focus of this scoping review was on research addressing the experiences and well-being of siblings of children with CKD. Methods Following scoping review methodology, five databases were searched for peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…While prior studies have highlighted the role of siblings in providing care and support29 31 our long-term analysis reveals a novel finding. Parents continue to seek sibling support even when it is no longer physically necessary, underscoring the enduring importance of siblings in promoting life participation, even after transplantation (Siblings, Topic 4).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…While prior studies have highlighted the role of siblings in providing care and support29 31 our long-term analysis reveals a novel finding. Parents continue to seek sibling support even when it is no longer physically necessary, underscoring the enduring importance of siblings in promoting life participation, even after transplantation (Siblings, Topic 4).…”
Section: Discussionmentioning
confidence: 70%
“…Our study is the first attempt to examine experiences and perceptions of families with long-term survivors of paediatric ESKD (including dialysis and transplantation) as a model for CMC from a long-term, biographical perspective. 29 Unique, comprehensive information of each individual story, exploring the factors that impact survivors' bilateral influences on their families and vice versa, revealed the desire for normality and the importance of siblings in the needed coping strategies of patients and their families. 30 31 Our key finding is patients, caregivers and siblings' desire for normality in daily life, each with varying perceptions of normality.…”
Section: Discussionmentioning
confidence: 99%
“…Depression or traumatic stress symptoms suggested by previous studies included in their review were not found of high importance, but the authors recognize that the self-reporting method could be the cause of variability in the results. [33].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on parent reports indicate negative aspects of their quality of life, because of their stress and the child’s diagnosis burden. Additionally, they indicate that the healthy siblings have a tendency to under report the difficulties they face in relation to their affected sibling, in order to formulate the answer they think is expected from them [ 31 , 32 , 33 ]. Another important limitation was that the order of birth of the child with a disability was not considered, as it is known that for a sibling relationship it is important whether a given child is the youngest or the oldest among siblings.…”
Section: Discussionmentioning
confidence: 99%